Islam dalam Pandangan Surat Kabar Jepang di Jawa (1916-1941) - Aji Cahyo Baskoro (Historia Madania: Jurnal Ilmu Sejarah, 2021)
This article aims to describe the views of Japanese newspapers published in Java between 1916 and 1941 on Islam as the most important aspects of the indigenous people’s life the island. The main sources used in this study were writings about Islam that appeared in three Japanese newspapers, namely Tjahaja Selatan, Java Nippo, and Sinar Selatan. In these writings, Islam is not only viewed from a spiritual perspective, but also political, as something that was always in conflict with the colonial government in particular, and the West in general. This view is influenced by developments related to Islam that occur both locally and globally. In the local context, at that time a modern Islamic movement was emerging in Java, while globally, there was also Pan-Islamism that spread and meet with Asianism in Japan.